Suitability assessment of fishing operation locations against predicted fishing ground maps during the western monsoon in the border area of Indonesian Fisheries Management Areas 712 and 713 - Vida Nikmatul Karimah; Kukuh Eko Prihantoko; Bambang Argo Wibowo; Ernowo Supriyatno Mudji Putra; Ayu Fitriani; Eli Nurlaela (Universitas Malikussaleh, 2026)
Knowledge of the dynamics of fishing grounds and fishing seasons is a major supporting factor for the success of fishing operations. This study aims to analyze fish catches based on fishing operation time, the distribution of fishing ground locations of Small Pelagic Purse Seine (PCPK), and their level of conformity to the Fishing Ground Forecast Map (PPDPI). This quantitative study analyzed 23 factual fishing ground coordinate points and catch data in the border areas of WPPNRI 712 and 713 during the West season. The results showed that the location of fishing grounds was distributed at 56.52% in WPPNRI 713 and 43.48% in WPPNRI 712. The catch was generally dominated by Scad (Decapterus spp.) at 42.95%, although there was a monthly variation in dominance where Sero fish dominated in January (57.50%). The Kappa test results produced a coefficient value of K = 0.184 with p = 0.311. This value indicates that the level of spatial agreement between the actual fishing ground locations and the PPDPI is in the very low category (slight agreement) and is not statistically significant (p > 0.05), so that the existing pattern of conformity is not different from random chance. This finding concludes that the PPDPI is currently not the main reference for fishermen in determining the actual fishing ground in fishing operations. Keywords: Fish; Pelagic Fish; Purse Seine; West Season